Attitudes of Saudi Mothers Towards Breastfeeding: A Cross–Sectional Survey in Taif Region, Saudi Arabia - Elbur, Abubaker Ibrahim; A., Yousif M.; Albarraq, Ahmed Abdulrahman; Abdallah, Mustafa A. (International Journal of Child Health and Nutrition, 2014)
Background: Mothers’ attitudes are strong predicators of choice of infant feeding method. This study was conducted to measure attitudes towards breastfeeding among Saudi mothers. Methods: A cross-sectional survey was conducted during April 2013 among Saudi nursing mothers in Taif Region; Kingdom of Saudi Arabia (KSA). Data was collected by trained pharmacy female students through face-to-face interview method using structured questionnaire. Mothers’ attitudes towards breastfeeding were assessed by The Iowa Infant Feeding Attitude Scale (IIFAS). Results: A total of 387 mothers were included of them 204 (52.7%) aged < 32 years and 334 (86.3%) were residents in the town. University or college graduates were 262 (67.7%). Overall 181 (46.8%) of the mothers had positive attitudes towards breastfeeding, while 206 (53.2%) held negative ones. Correlating mothers’ total attitudes towards breastfeeding to their demographics showed that; out of the mothers aged < 32 years 118 (57.8%) had significantly more positive attitudes than older ones (aged > 32 years) 63 (34.4%), (P < 0.001). Cross tabulation of the method of infant feeding and mothers’ total attitudes towards breastfeeding showed that mothers used formula feeding or mixed feeding method 120 (49.0%) had significantly positive attitudes towards breastfeeding more than breastfeeding ones 61(43.0%), (P =0.025). Conclusion: The rate of exclusive breastfeeding was low. Positive attitudes towards breastfeeding was found to be more among mothers used formula or mixed feeding method. Educational interventions are needed to raise awareness and upgrade mothers’ knowledge on infant breastfeeding.